The message of Daniel : the Lord is King - Wallace, Ronald S. (Leicester, UK : IVP, 1979)
Includes bibliographical references.
Copy two : "The Bible Speaks Today series has been placed in the Emmaus Bible College Library in memory of Gordon W. Craig, 1926-1990"
Keywords: Bible. -- commentaries